Neonatal Amygdala Volumes and the Development of Self-Regulation from Early Infancy to Toddlerhood - Nolvi Saara; Tuulari Jetro J.; Pelto Juho; Bridgett David J.; Eskola Eeva; Lehtola Satu J.; Hashempour Niloofar; Korja Riikka; Kataja Eeva-Leena; Saunavaara Jani; Parkkola Riitta; Lähdesmäki Tuire; et al. (American Psychological Association, 2022)
Objective: At the broadest level, self-regulation refers to a range of separate, but inter-related, processes (e.g., working memory, inhibition, emotion regulation) central for the regulation of cognition, emotion and behaviour that contribute to a plethora of health and mental health outcomes. Self-regulation skills develop rapidly in early childhood, but their neurobiological underpinnings are not yet well understood. The amygdala is one key structure in negative emotion generation that may disrupt self-regulation. In the current study, we investigated the associations between neonatal amygdala volumes and mother-reported and observed child self-regulation during the first three years of life. We expected that larger neonatal amygdala volumes would be related to poorer self-regulation in children.
Method: We measured amygdala volumes from MRI performed at age M=3.7±1.0. We examined the associations between the amygdala volumes corrected for intracranial volume and a) parent-reported indicators of self-regulation at 6, 12 and, 24 months (N=102) and b) observed, task-based indicators of self-regulation (working memory and inhibitory control) at 30 months of age in a smaller subset of participants (N=80).
Results: Bilateral neonatal amygdala volumes predicted poorer working memory at 30 months in girls, whereas no association was detected between amygdalae and inhibitory control or parent-reported self-regulation. The left amygdala by sex interaction survived correction for multiple comparisons.
Conclusions: Neonatal amygdala volume is associated with working memory, particularly among girls, and the association is observed earlier than in prior studies. Moreover, our findings suggest that the neural correlates for parent-reported, compared to observed early life self-regulation, may differ.